An Investigation Of The Relationship Between Corporate Governance Of Fund Management Firms And Performance Of Unit Trusts In Malaysia - Kee, Yan Herng (2021)
This purpose of this research is to examine the corporate governance mechanisms and the influence on the performance of unit trusts in Malaysia. The corporate governance mechanisms selected for the study are board size, number of non-executive directors, number of independent directors, and gender diversification, to measure the relationship and how they contribute towards the unit trust performance. The performance of unit trust will be measure by Total Annual Return for each unit trust. The study focused on the unit trusts which run by 23 fund management firms in Malaysia with at least provide two equity funds. The sample size is total 275 equity fund. The time frame chosen for the research was the year 2020. Cross-sectional data analysis was applied for this research which is multiple regression. The researcher found that corporate governance mechanisms which is number of non-executive directors and gender diversification have a significant relationship with the performance of unit trusts. However, the researcher also suggests future researchers can explore other corporate governance mechanisms for this study, and policymakers are still advised to strengthen the code of corporate governance in Malaysia to improve the performance of unit trust.